2008
DOI: 10.1002/pen.21171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyol molecular weight on properties of benzoxazine–urethane polymer alloys

Abstract: Recently, a new thermoset resin namely benzoxazine (BA) resin has been developed. The polymer possesses several outstanding properties, such as, ease of synthesis, low viscosity, near‐zero shrinkage, lack of by‐product upon curing, high thermal stability, and high mechanical property. Moreover, the benzoxazine resins can be alloyed with various types of resins because of the various function groups in their structure. In this work, urethane elastomer (PU) is used to enhance toughness of the polybenzoxazine. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 12 publications
7
39
0
2
Order By: Relevance
“…Interestingly, the synergistic behavior in T g of those polymer hybrids was observed at 50 wt% of BA‐a content, which was also observed in PU and PBA network as reported by in this work. The same synergistic behavior was also reported in thermally cured copolymers of these two families of polymers and was explained as due to the complementary property of the two polymers, i.e., the enhancement in crosslink density in the PBA fraction by the presence of the PUA and the improvement in network flexibility of PU by the presence of the more rigid PBA [].…”
Section: Resultssupporting
confidence: 57%
“…Interestingly, the synergistic behavior in T g of those polymer hybrids was observed at 50 wt% of BA‐a content, which was also observed in PU and PBA network as reported by in this work. The same synergistic behavior was also reported in thermally cured copolymers of these two families of polymers and was explained as due to the complementary property of the two polymers, i.e., the enhancement in crosslink density in the PBA fraction by the presence of the PUA and the improvement in network flexibility of PU by the presence of the more rigid PBA [].…”
Section: Resultssupporting
confidence: 57%
“…In addition, there is no by-product generated when curing that leads to no void in the final products. Alloying the brittle polybenzoxazine with other flexible monomers or polymers have been reported to enhance its crosslink density and mechanical properties in many blending systems such as benzoxazine/epoxy copolymer, 7,9,10 benzoxazine/ epoxy/phenolic ternary systems, [11][12][13] poly(benzoxazine-urethane) alloys, 8,[14][15][16] polybenzoxazine/dianhydride copolymer, 17 polybenzoxazine/ polycaprolactone blends. Moreover, it has been reported that the polymer possesses high thermal stability, high glass transition temperature (T g ) with low water absorption and near zero shrinkage or expansion.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Furthermore, polybenzoxazines have good electrical insulating properties with ease of processing due to low melt viscosity of the polymers. Rimdusit et al 8 reported the synergistic behaviors of glass transition temperature for the systems of benzoxazine and epoxy hybrids. For example, BA-a type benzoxazine monomer has been commercialized by Shikoku Chemical Corporation, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…The first strategy is by utilizing a novel molecular design of benzoxazine resins such as a synthesis of linear aliphatic diamine‐based benzoxazine and a utilization of high molecular weight benzoxazine precursors. 4 Second method is by alloy formation or copolymerization with flexible resins or polymers such as urethane elastomer, 5–7 flexible epoxy, 6, 8 poly (ε‐caprolactone), 9 poly(imide‐siloxane), 10 and polydimethylsiloxane. 11 The latter strategy is a relatively versatile and simple method to improve mechanical property or thermal stability of polybenzoxazine.…”
Section: Introductionmentioning
confidence: 99%